Mansfield Park - Austen, Jane (Alfred A. Knopf, 1994)
This popular series of readers has now been completely revised and updated, using a new syllabus and new word structure lists. Readability has been ensured by means of specially designed computer software. Words that are above level but essential to the story are explained within the text, illustrated, and then reused for maximum reinforcement